Analisis Penerapan Metode Ummi dalam Meningkatkan Kemampuan Membaca Al-Qur’an - Sabilla, Najwa; Zainab, Ummu; Afifah, Fatin (Journal of Sustainable Education, 2025)
This research aims to analyze the application of the Ummi method in improving the ability to read the Qur'an, particularly in terms of fluency and accuracy of recitation. The background of this research is the reality that many children and adults are still unable to read the Qur'an well and accurately. This is often caused by a less effective learning approach that does not adequately address emotional aspects and intensive practice in learning. The Ummi Method is a relatively new approach but has been used by more than a thousand educational institutions in Indonesia. This research employs a library research approach, examining various sources of literature such as scientific journals, books, and previous research findings. The study results show that the Ummi method adopts a learning approach that combines the direct method (reading directly without spelling), repetition, and affection as its pedagogical foundation. In addition, this method is equipped with seven basic programs such as tashih, tahsin, certification, coaching, supervision, munaqasyah, and khotaman, which aim to ensure the overall quality of learning. This study concludes that the Ummi method can significantly improve the quality of students' Quran recitation if applied consistently and supported by the readiness of teachers and good institutional management. However, challenges are still found in the limitations of time, teacher creativity, and the character conditions of the students. Therefore, the success of this method is highly determined by the collaboration of teachers, parents, and a supportive learning environment